The lord of the rings, the return of the king - Jackson, Peter, 1961-; Wood, Elijah, 1981-; McKellen, Ian.; Tyler, Liv.; Mortensen, Viggo, 1958-; Astin, Sean.; Lesnie, Andrew, 1956-2015.; Shore, Howard; Tolkien, J. R. R. (John Ronald Reuel), 1892-1973.; New Line Home Video (Firm); Warner Home Video (Firm) ([United States] : New Line Home Entertainment ; Burbank, CA : Distributed by Warner Home Video, 2004)
The Fellowship divides to conquer, as Frodo and Sam, with the help and hindrance of Gollum, continue on their way to Mount Doom. Gandalf and Pippin ride to Minas Tirith to help defend Gondor, while Merry remains with Eowyn and the other Rohan fighters. Aragorn, Legolas, and Gimli seek aid from those that live in the Cursed Mountains. All these battles have one ultimate goal in mind: to distract the Eye of Sauron and buy Frodo as much time as possible in order to destroy the One Ring.
Title from container.
Based on the book by J.R.R. Tolkien.
Special features: 50 minutes of new and extended scenes added to the feature; audio commentary; DVD-ROM features; documentaries; Easter eggs; interactive maps; in-depth interviews with the cast and crew; behind-the-scenes footage; production meetings; footage captured at the film's premieres around the world.
Director of photography, Andrew Lesnie ; editor, Jamie Selkirk ; music, Howard Shore ; costume designers, Ngila Dickson, Richard Taylor ; production designer, Grant Major ; visual effects supervisor, Jim Rygiel ; special make-up, creature, miniature and digital effects, Weta Ltd.
Elijah Wood, Ian Mckellen, Liv Tyler, Viggo Mortensen, Sean Astin, Cate Blanchett, John Rhys-Davies, Bernard Hill, Christopher Lee, Billy Boyd, Dominic Monaghan, Orlando Bloom, Hugo Weaving, Miranda Otto, David Wenham, Brad Dourif, Karl Urban, John Noble, Andy Serkis, Ian Holm, Sean Bean.
MPAA rating: PG-13; for intense epic battle sequences and frightening images.
Keywords: Baggins, Frodo -- Drama; Middle Earth (Imaginary place) -- Drama; Kings and rulers -- Drama; Rings -- Drama; Baggins, Frodo (Personaje literario) -- Teatro; Reyes y soberanos -- Teatro; Feature films; Fantasy -- Feature; Video recordings for hard of hearing people